Open source innovation: Characteristics and applicability outside the software industry - Christina Raasch; Cornelius Herstatt; Nizar Abdelkafi (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2008)
Motivation of this paper is to discuss that the open source model of innovation does not only seem practical in the software industry, but also in various other industrial contexts. We develop the concept of Open Source Innovation (OSI) as a generalisation of the open source model of software development (OSS). Our definition centres on the collaboration of volunteers and the free revelation of knowledge between actors. Since OSI exhibits important differences to several related concepts in the literature, we conclude that it is an innovation model in its own right, deserving more attention and research. We further proceed to identify aspects affecting the application of the OSI model in industry practices, grouping them into economic, technical, legal, and social factors. Based on these results as well as expert interviews, we find that the applicability of OSI is primarily determined by the characteristics of, first, the innovation object and, second, the group of contributors, rather than the industrial sector. Finally, we advance propositions on the employment of OSI in industrial practice, relating its feasibility to the innovation object and the group of contributors.
Keywords: 650